Lyrics of Kawih Tanah Sunda by Koko Koswara as a Media for Learning Cultural Literacy for Students in Junior High School - Muliawati, Ema Siti; Maryanti, Rina (ASEAN Journal of Educational Research and Technology, 2022)
Indonesia has been carrying out online learning for more than 2 years in an effort to break the chain of transmission of Covid-19. With the community service program, it is hoped that there will be an increase in student interest in learning and make it easier for educators and parents to carry out online learning activities. Included in the learning of Kawih "land of Sunda" by Koko Koswara in class VIII junior high school is done online. The method in this study uses quantitative research. The results of this study are still many students who do not know the Sundanese kawih. Students' understanding of the material for the lyrics of the kawih song "Land of Sunda by Koko Koswara" can be improved by providing material via powerpoint or youtube which is done online from using the googlemeet application with educators. The results of the research show that the average posttest score of students is 67.86% greater than the average pretest score of 27.84% so the difference is 40.02%. Therefore, Core competencyta can increase students' interest in cultural literacy.